Examining How School Environment and Teacher Competence Affect Student Learning Motivation at MA Al Fatich Tambak Osowilangun Surabaya - Abdul Latif; Didit Darmawan (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
Learning activities and educational quality are at the centre of the educational stage. The quality of education can be assessed based on the discipline of students in the school or community environment and the competence of teachers. This study aims to reveal the influence of the school environment and teacher competence on student learning motivation. Quantitative research methods collect data through surveys with questionnaires and direct observation of students. The research results show that a conducive school environment and high teacher competence have contributed positively to student learning motivation. Factors such as positive relationships between teachers and students, a supportive classroom atmosphere, adequate learning facilities, and the use of innovative teaching methods form a motivating environment for students. Teacher competence to understand student needs, provide appropriate challenges, and create positive relationships also plays an important role in increasing student learning motivation. It is hoped that these results can serve as a guide for educational policies and teacher professional development to increase student learning motivation in the school environment.